2022
DOI: 10.1186/s13018-022-03068-7
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge structure and emerging trends on osteonecrosis of the femoral head: a bibliometric and visualized study

Abstract: Background Osteonecrosis of the femoral head (ONFH) is a common disabling disease with considerable social and economic impacts. Although extensive studies related to ONFH have been conducted in recent years, a specific bibliometric analysis on this topic has not yet been performed. Our study attempted to summarize the comprehensive knowledge map, development landscape, and future directions of ONFH research with the bibliometric approach. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 42 publications
0
34
0
Order By: Relevance
“…The above results reflect that the United States has made tremendous contribution and established its leading position in the domain of BMDM research. In addition to the BMDM research subject, earlier bibliometric studies revealed that the United States also had the highest number of publications in other areas of BM or DM researches (31,32,34). As for countries or institutions collaboration analysis, it can be seen from Figure 3B that the United States collaborated most closely with China, Italy, and Canada.…”
Section: Countries and Institutionsmentioning
confidence: 87%
See 4 more Smart Citations
“…The above results reflect that the United States has made tremendous contribution and established its leading position in the domain of BMDM research. In addition to the BMDM research subject, earlier bibliometric studies revealed that the United States also had the highest number of publications in other areas of BM or DM researches (31,32,34). As for countries or institutions collaboration analysis, it can be seen from Figure 3B that the United States collaborated most closely with China, Italy, and Canada.…”
Section: Countries and Institutionsmentioning
confidence: 87%
“…As can be seen from Supplementary Table 1, "glycation endproduct" was the largest cluster (#0), followed by "oxidative stress" (#1), and "energy metabolism" (#2). In addition, the timeline chart could cluster references and take time into account, which is convenient for us to understand the period of a particular topic and explore the evolution track of this field (34). According to mean year of these clusters, we can see that the research hotspots have shifted to "high glucose environment" (#8), "glycation end-product" (#0), and "sodium-glucose cotransporter" (#7).…”
Section: References Co-citation Analysismentioning
confidence: 99%
See 3 more Smart Citations